2014
DOI: 10.4236/wjns.2014.45051
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trace Metals and Environmental Factors in the Onset and Progression of Schizophrenia in Pakistani Population

Abstract: Exposure to toxic chemicals appears to be one of the major factors in the onset of Schizophrenia. Present study was designed to find out the association of socioeconomic , clinical and heavy metals such as chromium (Cr), lead (Pb) copper (Cu), zinc (Zn), iron (Fe), manganese (Mn) selenium (Se) and arsenic (As) as the principle environmental factors that appear to impact schizophrenic condition in Pakistani population. In this study we have tried to expose some factors such as drug abuse, marital status, educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…In recent years there have been more and more studies regarding the contribution of various metals to schizophrenia that have reported conflicting results about the concentration of Mn in patients [14,20,[22][23][24][25][26][27]. Eight studies were taken under consideration, with one reporting elevated levels of Mn [23], two showing no significant difference [22,25], and the rest stating that Mn concentration in patients with schizophrenia was lower than in controls [14,20,22,26,27]. Liu et al (2015) observed that higher concentrations of manganese (>3.95 µg/L) in serum were associated with an increased risk of schizophrenia (OR=19.269 (95% CI: 1.436-258.626)) [23].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years there have been more and more studies regarding the contribution of various metals to schizophrenia that have reported conflicting results about the concentration of Mn in patients [14,20,[22][23][24][25][26][27]. Eight studies were taken under consideration, with one reporting elevated levels of Mn [23], two showing no significant difference [22,25], and the rest stating that Mn concentration in patients with schizophrenia was lower than in controls [14,20,22,26,27]. Liu et al (2015) observed that higher concentrations of manganese (>3.95 µg/L) in serum were associated with an increased risk of schizophrenia (OR=19.269 (95% CI: 1.436-258.626)) [23].…”
Section: Resultsmentioning
confidence: 99%
“…Then solution was placed on a hot plate, until clear solution was obtained. The resulting clear solution was cooled down at room temperature and 5 ml HNO 3 0.1 N, was added and a volume of 50 ml from sample was prepare by using deionized water [1] . After chemical digestion and preparation, the samples were read by using ICP-OES [2] , [3] , [4] , [5] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…A large number of people in Pakistan, mostly men, are addicted to tobacco, cannabis, betel nut, charas, and other illicit drugs [ 14 ]. Repeated administration of these stimulants at a younger age (<15 years) increases the likelihood of developing SCZ [ 15 ]. This finding is consistent with those of another study, which suggested that the proportion of Pakistani people who use cannabis and exhibit schizophrenic symptoms is significantly higher among men than women.…”
Section: Prevalence Of Schizophreniamentioning
confidence: 99%
“…However, published studies have demonstrated an association between NRG1 and TNF -α gene mutations and SCZ in the Pakistani population [ 81 ]. Earlier, Nawaz et al [ 14 ] and Naqvi et al [ 82 ] demonstrated that the NRG1 genetic variant SNP rs35753505 and polymorphism8nrg433E1006 plays an important role in conferring susceptibility to SCZ in the Pakistani population and may represent a potential antipsychotic drug target in such patients [ 15 ].Moreover, Amir et al provided strong evidence that supports the role of CACNA1C , GRM3 , and DRD2 genes as schizophrenia susceptibility genes in the Pakistani population [ 74 ]. Nevertheless, one study has shown that some genetic variants rs1801028 and rs6277 of DRD2 are not associated with schizophrenia in the Pakistani population [ 83 ].…”
Section: Genetics Of Schizophreniamentioning
confidence: 99%